Air hazardous substance adhesion inhibiting method

By applying metal oxide with a specific particle size to the skin to create nano-sized unevenness, the method effectively suppresses the adhesion of atmospheric harmful substances, addressing the limitations of existing cosmetics in this regard.

JP2025061875APending Publication Date: 2025-04-11KAO CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025012029
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-06-06
Filing Date
2025-01-28
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing skin care cosmetics are unable to effectively prevent the adhesion of atmospheric harmful substances such as PM2.5, pollen, and yellow sand to the skin, despite their ability to adsorb and neutralize these substances.

Method used

Applying a specific amount of metal oxide with an average primary particle diameter of 800 nm or less to the skin, creating nano-sized unevenness on the skin surface, thereby suppressing the adhesion of atmospheric harmful substances.

Benefits of technology

The method effectively suppresses the adhesion of atmospheric harmful substances to the skin, particularly fine particulate matters, by reducing the contact area between the substances and the skin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025061875000004
    Figure 2025061875000004
  • Figure 2025061875000005
    Figure 2025061875000005
  • Figure 2025061875000001
    Figure 2025061875000001
Patent Text Reader

Abstract

To provide an air hazardous substance adhesion inhibiting method capable of effectively suppressing air hazardous substances from adhering to the skin.SOLUTION: Provided is an air hazardous substance adhesion inhibiting method which inhibits air hazardous substances from adhering to the skin by applying, to the skin, a metal oxide (A) having an average primary particle diameter dA of 800 nm or less in an amount of 0.03 mg / cm2 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for suppressing adhesion of atmospheric hazardous substances. [Background technology]

[0002] In recent years, harmful substances suspended in the air, such as pollen from cedars and cypresses, soot, dust, and other air pollutants, and yellow sand (hereinafter also referred to as "air hazardous substances"), have become a problem because they cause various health damages to the human body. Among the air hazardous substances, particulate matter with a diameter of 2.5 μm or less, called PM2.5, is composed of carbon components, sulfates, nitrates, ammonium salts, and the like, and it is known that PM2.5 and yellow sand cause diseases of the circulatory system and respiratory system when inhaled. It has also been pointed out that PM2.5, pollen, and yellow sand cause skin troubles by adhering to or penetrating the skin. For example, Non-Patent Document 1 contains an academic report on the damage caused by PM2.5 to the skin. Therefore, there is a strong demand for cosmetics that protect the skin from air hazardous substances. For example, Patent Document 1 describes a skin care cosmetic that contains a specific amount of magnesium aluminometasilicate and a specific amount of an ultraviolet protection agent as a skin care cosmetic that protects the skin from external stimuli such as air pollutants. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2014 / 136993 [Non-patent literature]

[0004] [Non-Patent Document 1] Shiraiwa et al., Nature Chemistry 3, 291-295 (2011) Summary of the Invention [Problem to be solved by the invention]

[0005] In the technology of Patent Document 1, it is described that magnesium aluminometasilicate adsorbs air pollutants by its adsorption ability and prevents them from reaching the skin, and even if an acidic substance adheres to the skin, it can neutralize it by its pH buffering ability, thereby reducing skin damage caused by these external stimuli. It is also described that UV protection agents effectively protect the skin from UV rays. Although such technology can reduce the effects of air pollutants on the skin, it does not prevent the adhesion of air pollutants to the skin, and there is room for improvement. An object of the present invention is to provide a method for inhibiting adhesion of atmospheric hazardous substances, which can effectively inhibit adhesion of atmospheric hazardous substances to the skin. [Means for solving the problem]

[0006] The inventors have discovered that the above-mentioned problems can be solved by focusing on the fact that adhesion of atmospheric harmful substances to the skin can be inhibited by applying a specific amount of a metal oxide having a specific average primary particle size to the skin and forming nano-sized irregularities on the skin surface, rather than by adsorbing air pollutants as shown in Patent Document 1. That is, the present invention has an average primary particle diameter d A A metal oxide (A) having a particle size of 800 nm or less is added at 0.03 mg / cm 2 As described above, a method for inhibiting adhesion of atmospheric hazardous substances to the skin is provided, in which the composition is applied to the skin to inhibit adhesion of atmospheric hazardous substances to the skin. Effect of the Invention

[0007] According to the method of the present invention, it is possible to effectively prevent atmospheric hazardous substances from adhering to the skin. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a schematic diagram showing a method for evaluating the effect of suppressing adhesion of atmospheric hazardous substances. [Diagram 2] FIG. 2 is a graph showing the results of the adhesion inhibition rate of air hazardous substances versus the coating amount of metal oxide (A) in Examples 1 to 9 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] [Methods for preventing the adhesion of harmful substances to the atmosphere] The method for suppressing the adhesion of atmospheric hazardous substances of the present invention is to A A metal oxide (A) having a particle size of 800 nm or less is added at 0.03 mg / cm 2 The above is a method of applying the agent to the skin to prevent harmful air substances from adhering to the skin. In the present invention, "harmful air substances" refers to air pollutants such as pollen from cedar, cypress, etc.; soot and smoke such as sulfur oxides, soot dust, nitrogen oxides, particulate matter, automobile exhaust gas, harmful air pollutants such as benzene, trichloroethylene, tetrachloroethylene, and particles containing volatile organic compounds (VOCs); and harmful substances suspended in the air such as yellow sand (including PM2.5). In the following description, the effect of the present invention in inhibiting adhesion of atmospheric hazardous substances will be referred to simply as "adhesion inhibiting effect."

[0010] The adhesion suppression method of the present invention is highly effective in suppressing adhesion of air hazardous substances, particularly air hazardous substances in the form of fine particles. Although the reason for this is unclear, it is believed that in the present invention, nano-sized irregularities are formed on the skin surface by applying a specific amount of a metal oxide having an average primary particle size within a specific range to the skin, thereby reducing the contact area when the air hazardous substances come into contact with the metal oxide, and thus effectively suppressing adhesion of the air hazardous substances.

[0011] <Metal oxide (A)> Average primary particle diameter d of metal oxide (A) A From the viewpoint of improving the adhesion suppression effect, the average primary particle diameter d is 800 nm or less, preferably 500 nm or less, more preferably 300 nm or less, even more preferably 200 nm or less, still more preferably 80 nm or less, and even more preferably 50 nm or less, and from the viewpoint of versatility, it is preferably 5 nm or more, more preferably 10 nm or more. AFrom the viewpoint of improving the adhesion suppression effect and from the viewpoint of versatility, the thickness is preferably 5 to 800 nm, more preferably 5 to 500 nm, even more preferably 5 to 300 nm, still more preferably 5 to 200 nm, even more preferably 5 to 80 nm, even more preferably 5 to 50 nm, and even more preferably 10 to 50 nm. The average primary particle diameter d A can be obtained from an image observed by a transmission electron microscope (TEM). Specifically, the maximum short diameter of 300 primary particles in the observed image is measured under conditions of a magnification of 50,000 times by TEM, and the number average value is calculated. Here, the maximum short diameter means the short diameter having the maximum length among the short diameters perpendicular to the long diameter when the metal oxide (A) has a shape other than a plate shape. When the metal oxide (A) is plate-shaped, the thickness of 300 primary particles in the observed image observed under the same conditions as above is measured, and the number average value is calculated. Specifically, it is measured by the method described in the examples.

[0012] The metal oxide (A) is not particularly limited as long as it is one that is commonly used in external preparations such as cosmetics. Specific examples include titanium oxide, zinc oxide, cerium oxide, aluminum oxide (alumina), magnesium oxide, calcium oxide, zirconium oxide, iron oxide, chromium oxide, etc. Among these, from the viewpoint of imparting ultraviolet protection ability, it is preferably one or more selected from the group consisting of titanium oxide, zinc oxide, and cerium oxide, and more preferably one or more selected from the group consisting of titanium oxide and zinc oxide. When the metal oxide (A) is titanium oxide, the crystal structure of the titanium oxide may be any of anatase type, rutile type, and brookite type, but from the viewpoint of versatility, the rutile type or anatase type is preferable.

[0013] The shape of the metal oxide (A) may be spherical, spindle-like, plate-like, needle-like, etc. Among these, from the viewpoint of improving the adhesion suppression effect, spherical, spindle-like and plate-like shapes are preferred. When the metal oxide (A) is titanium oxide, it is preferably spindle-shaped from the viewpoint of improving the adhesion suppression effect. When the metal oxide (A) is zinc oxide, it is preferably spherical or plate-shaped from the viewpoint of improving the adhesion suppression effect. The form of the metal oxide (A) is the average primary particle diameter d A As long as the above-mentioned range is satisfied, the toner may be in the form of primary particles, or may be in the form containing aggregates (secondary particles) formed by aggregation of primary particles.

[0014] The metal oxide (A) may be surface-untreated or surface-treated, but from the viewpoint of increasing the dispersibility of the metal oxide (A) when used in external preparations such as cosmetics and improving the adhesion suppression effect, the metal oxide (A) is preferably surface-treated. Examples of the surface treatment include hydrophobization and hydrophilization.

[0015] Examples of hydrophobic treatments include silicone treatment, alkylalkoxysilane treatment, fatty acid treatment, treatment with fluorine-containing compounds such as perfluoroalkyl phosphate esters, perfluoroalcohols, and perfluoroalkylalkoxysilanes, treatment with amino acids such as N-acylglutamic acid, and alkyl phosphate ester treatment. Among these, from the viewpoints of increasing the dispersibility of the metal oxide (A) in the cosmetic and improving the adhesion suppression effect, silicone treatment, alkylalkoxysilane treatment, and fatty acid treatment are preferred.

[0016] Examples of surface treatment agents used in silicone treatment include various silicone oils such as methylpolysiloxane, dimethylpolysiloxane, methylphenylpolysiloxane, methylhydrogenpolysiloxane, methylcyclopolysiloxane, dodecamethylcyclohexasiloxane, tetradecamethylhexasiloxane, dimethylsiloxane / methyl(polyoxyethylene)siloxane / methyl(polyoxypropylene)siloxane copolymer, dimethylsiloxane / methyl(polyoxyethylene)siloxane copolymer, dimethylsiloxane / methyl(polyoxypropylene)siloxane copolymer, dimethylsiloxane / methylcetyloxysiloxane copolymer, dimethylsiloxane / methylstearoxysiloxane copolymer, and alkyl acrylate / dimethicone copolymer. Among these, methylhydrogenpolysiloxane and dimethylpolysiloxane are preferred from the viewpoint of increasing the dispersibility of the metal oxide (A) in the cosmetic and improving the adhesion suppression effect.

[0017] As the surface treatment agent used in the alkylalkoxysilane treatment, from the viewpoint of increasing the dispersibility of the metal oxide (A) in the cosmetic and improving the adhesion suppression effect, those having a linear or branched alkyl group having from 6 to 20 carbon atoms are preferred, and octyltriethoxysilane and octyltrimethoxysilane are more preferred. Examples of the surface treatment agent used in the fatty acid treatment include linear or branched fatty acids having from 12 to 22 carbon atoms. Among them, from the viewpoint of increasing the dispersibility of the metal oxide (A) in the cosmetic and improving the adhesion suppression effect, linear or branched higher fatty acids having from 14 to 22 carbon atoms are preferred, linear or branched higher fatty acids having from 16 to 20 carbon atoms are more preferred, and stearic acid and isostearic acid are even more preferred.

[0018] Commercially available hydrophobically treated metal oxides (A) include "JR-800S" (silicone-treated titanium oxide), "MPY-70M" (silicone-treated titanium oxide), "MZ-504R3M" (silicone-treated zinc oxide), "MT-600KS" (silicone-treated zinc oxide), "MT-100TV" (stearic acid-treated titanium oxide), and "MT-100Z" (stearic acid-treated titanium oxide) manufactured by Teika Co., Ltd.; "MPT-171" (stearic acid-treated titanium oxide) manufactured by Ishihara Sangyo Kaisha, Ltd.; and "D-F" manufactured by Daito Kasei Kogyo Co., Ltd. ZN" (zinc oxide treated with silicone); Sakai Chemical Industry Co., Ltd.'s "STR-100A-LP" (titanium oxide treated with silicone), "FINEX-50-LPTM" (zinc oxide treated with silicone), "FINEX-30-OTS" (zinc oxide treated with octyltriethoxysilane), "STR-100C-LF" (titanium oxide treated with stearic acid), "STR-100W-OTS" (titanium oxide treated with octyltriethoxysilane), and "FINEX-50-OTS" (zinc oxide treated with octyltriethoxysilane).

[0019] Examples of the hydrophilization treatment include treatments with hydrous silica, hydrous oxides, oxides or hydroxides of metals such as aluminum and zirconia, water-soluble polymers such as polyacrylic acid, alginic acid or salts thereof, etc. Among these, one or more treatments selected from the group consisting of hydrous silica treatment and aluminum hydroxide treatment are preferred. Commercially available hydrophilically treated metal oxides (A) include "MT-100WP" (hydrated silica-treated titanium oxide) manufactured by Teika Co., Ltd., "STR-100W" (hydrated silica-treated titanium oxide), "STR-100C" (aluminum hydroxide-treated titanium oxide), and "FINEX-33W" (hydrated silica-treated zinc oxide) manufactured by Sakai Chemical Industry Co., Ltd.

[0020] The above-mentioned surface treatment agents may be used alone or in combination of two or more. The amount of the hydrophobization or hydrophilization treatment is preferably 0.1% by mass or more, and preferably 40% by mass or less, more preferably 30% by mass or less, based on the metal oxide (A), from the viewpoints of increasing the dispersibility of the metal oxide (A) in the cosmetic and improving the adhesion suppression effect. In addition, when the metal oxide (A) has been subjected to a hydrophobic or hydrophilic treatment, the mass, coating amount and average primary particle diameter d A is the mass including the surface treatment agent, the coating amount, and the average primary particle diameter d A means...

[0021] When the metal oxide (A) is titanium oxide, the content of TiO2 in the titanium oxide is preferably 60 mass% or more, more preferably 70 mass% or more, and preferably 100 mass% or less, from the viewpoint of improving the adhesion suppression effect. When the metal oxide (A) is zinc oxide, the ZnO content in the zinc oxide is preferably 60 mass % or more, more preferably 70 mass % or more, and preferably 100 mass % or less, from the viewpoint of improving the adhesion suppression effect.

[0022] From the viewpoints of increasing the dispersibility of the metal oxide (A) in the cosmetic and improving the adhesion suppression effect, it is preferable that the metal oxide (A) has been surface-treated to be hydrophobized or hydrophilized, more preferably the metal oxide (A) has been surface-treated to be hydrophobized, still more preferably one or more selected from the group consisting of hydrophobized titanium oxide (hereinafter also referred to as "hydrophobized treated titanium oxide") and hydrophobized zinc oxide (hereinafter also referred to as "hydrophobized treated zinc oxide"), even more preferably one or more selected from the group consisting of silicone-treated titanium oxide, silicone-treated zinc oxide, fatty acid-treated titanium oxide, fatty acid-treated zinc oxide, alkylalkoxysilane-treated titanium oxide, and alkylalkoxysilane-treated zinc oxide, still more preferably one or more selected from the group consisting of silicone-treated titanium oxide, silicone-treated zinc oxide, fatty acid-treated titanium oxide, and alkylalkoxysilane-treated zinc oxide.

[0023] In the present invention, the method of applying the metal oxide (A) to the skin can be to apply it directly without using a solvent or the like, but it can also be applied by appropriately mixing with a solvent, oil, or additive that is generally used in external preparations such as cosmetics depending on the form of use or purpose. Here, "applying to the skin" includes not only directly applying the metal oxide (A) to the skin surface with the hands or the like, but also attaching the metal oxide (A) to the skin surface by spraying or the like. In the present invention, from the viewpoint of improving the uniformity of the coating film when applied to the skin and improving the adhesion-inhibiting effect, it is preferred to previously stir and mix the metal oxide (A) with a solvent or oil to disperse the metal oxide (A) in the solvent or oil, and then apply the resulting mixture to the skin.

[0024] Examples of the solvent used when applying the metal oxide (A) to the skin include monohydric or polyhydric alcohols having 1 to 6 carbon atoms, such as ethanol, glycerin, 1,3-butylene glycol, propylene glycol, and sorbitol. Among these, it is preferable to use ethanol from the viewpoint of versatility. The amount of the solvent, expressed as the mass ratio of the metal oxide (A) to the solvent [metal oxide (A) / solvent], is preferably 0.02 or more, more preferably 0.03 or more, even more preferably 0.04 or more, from the viewpoint of improving the adhesion suppression effect, and is preferably 1 or less, more preferably 0.7 or less, even more preferably 0.5 or less.

[0025] The oil used when applying the metal oxide (A) to the skin is preferably a volatile oil. In this specification, "volatile" means that the amount of evaporation at 25°C in 6 hours is more than 20%, as measured by the following method. Measurement method: Place a 90mm diameter filter paper in a 120mm diameter glass petri dish, place 1g of sample on the filter paper, and store in a room at 65% RH (25℃) for 6 hours. Measure the mass of the sample before and after storage, and calculate the amount of evaporation using the following formula. Evaporation amount (%) = (sample mass before storage - sample mass after storage) / sample mass before storage x 100 Examples of the volatile oil include volatile silicone oil and volatile hydrocarbon oil.

[0026] The volatile silicone oil in the present invention is a silicone oil having a kinetic viscosity of 5 mm at 25°C. 2 The kinematic viscosity at 25° C. can be measured by an Ubbelohde viscometer in accordance with ASTM D 445-46T or JIS Z 8803. Volatile silicone oils include linear organopolysiloxanes and cyclic organopolysiloxanes. Specific examples of linear organopolysiloxanes include octamethyltrisiloxane, decamethyltetrasiloxane, dodecamethylpentasiloxane, and 1,1,1,3,5,5,5-heptamethyl-3-[(trimethylsilyl)oxy]-trisiloxane. Examples of the cyclic organopolysiloxane include 4- to 6-membered cyclic siloxanes having an alkyl group having 1 to 5 carbon atoms as a substituent, and specific examples include octamethylcyclotetrasiloxane and decamethylcyclopentasiloxane. Commercially available volatile silicone oils include Shin-Etsu Chemical Co., Ltd.'s "KF-96A-1cs" (octamethyltrisiloxane), "KF-96L-1.5cs" (decamethyltetrasiloxane), "KF-96L-2cs" (dodecamethylpentasiloxane), "KF-995" (decamethylcyclopentasiloxane), and "TMF-1.5" (1,1,1,3,5,5,5-heptamethyl-3-[(trimethylsilyl)oxy]-trisiloxane); and Dow Corning Toray Co., Ltd.'s "SH200C Fluid 1cs" (octamethyltrisiloxane), "SH200C Fluid 1.5cs" (decamethyltetrasiloxane), "SH200C Fluid 2cs" (dodecamethylpentasiloxane), and "SH245 Fluid" (decamethylcyclopentasiloxane); Momentive Performance Materials' "TSF405" (decamethylcyclopentasiloxane), etc.

[0027] As the volatile hydrocarbon oil, saturated or unsaturated hydrocarbon oils having 8 to 16 carbon atoms are preferred, and examples thereof include paraffin-based hydrocarbon oils such as n-decane, n-undecane, and n-dodecane; isoparaffin-based hydrocarbon oils such as isodecane, isododecane, and hydrogenated polyisobutene (light liquid isoparaffin); and cyclic paraffin hydrocarbon oils such as cyclodecane and cyclododecane.

[0028] The amount of the oil agent, expressed as the mass ratio of the metal oxide (A) to the oil agent [metal oxide (A) / oil agent], is preferably 0.02 or more, more preferably 0.03 or more, even more preferably 0.04 or more, from the viewpoint of improving the adhesion suppression effect, and is preferably 1 or less, more preferably 0.7 or less, even more preferably 0.5 or less.

[0029] The amount of metal oxide (A) applied to the skin surface is 0.03 mg / cm from the viewpoint of improving the adhesion suppression effect. 2 or more, preferably 0.04 mg / cm 2 More preferably, 0.05 mg / cm 2 More preferably, 0.07 mg / cm 2 More preferably, 0.10 mg / cm 2 More preferably, 0.15 mg / cm 2 From the viewpoints of economy and usability when used as an external preparation, the concentration is preferably 0.8 mg / cm 2 Less than 0.7 mg / cm, more preferably 0.7 mg / cm 2 More specifically, the amount of the metal oxide (A) applied to the skin surface is preferably 0.03 to 0.8 mg / cm from the viewpoint of improving the adhesion suppression effect, as well as from the viewpoints of economy and usability when used as an external preparation. 2 , more preferably 0.04 to 0.8 mg / cm 2 , and more preferably 0.05 to 0.8 mg / cm 2 , and even more preferably 0.07 to 0.8 mg / cm 2 , and even more preferably 0.10 to 0.8 mg / cm 2 , and even more preferably 0.15 to 0.8 mg / cm 2, and even more preferably 0.15 to 0.7 mg / cm 2 It is.

[0030] In the present invention, the metal oxide (A) can be applied, for example, by blending it with an external preparation to be applied to the skin or hair. From the viewpoint of adhesion suppression effect, the external preparation is preferably a cosmetic preparation, more preferably a skin cosmetic preparation. The form of the topical agent may be an aqueous type having a single aqueous phase as the dispersion medium, an oil-based type having a single oil phase as the dispersion medium, an oil-in-water type (O / W type), a water-in-oil type (W / O type), or the like, and may be appropriately selected. The dosage form of the topical preparation is not particularly limited, and it may be any dosage form such as liquid, foam, paste, cream, solid, etc. The topical preparation in the form of a liquid, foam, paste, cream, or solid can usually be applied as it is by coating, spraying, or the like. In addition to the metal oxide (A), the topical preparation may appropriately contain cosmetic ingredients or medicinal ingredients used according to the purpose of the topical preparation, or ingredients normally used in topical preparations such as skin cosmetics, within the scope of the present invention. Examples of such ingredients include antioxidants, ultraviolet absorbers, surfactants, thickeners, oils, pH adjusters, bactericides, anti-inflammatory agents, preservatives, colorants, chelating agents, moisturizers, pearlescent agents, ceramides, antiperspirants, fragrances, etc., other than the metal oxide (A).

[0031] The content of the metal oxide (A) in the topical preparation is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 7% by mass or more from the viewpoint of improving the adhesion suppression effect, and is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 35% by mass or less from the viewpoints of economy and the feeling of use when used as a topical preparation.

[0032] When the topical preparation is an oil-in-water (O / W) type, the amount of metal oxide (A) applied to the skin surface is 0.03 mg / cm from the viewpoint of improving the adhesion suppression effect. 2 or more, preferably 0.04 mg / cm 2 More preferably, 0.05 mg / cm 2More preferably, 0.07 mg / cm 2 More preferably, 0.10 mg / cm 2 More preferably, 0.15 mg / cm 2 From the viewpoints of economy and usability when used as an external preparation, the concentration is preferably 0.8 mg / cm 2 Less than 0.7 mg / cm, more preferably 0.7 mg / cm 2 More preferably, 0.5 mg / cm 2 More preferably, 0.3 mg / cm or less. 2 More specifically, the amount of the metal oxide (A) applied to the skin surface is preferably 0.03 to 0.8 mg / cm from the viewpoint of improving the adhesion suppression effect, as well as from the viewpoints of economy and usability when used as an external preparation. 2 , more preferably 0.04 to 0.8 mg / cm 2 , and more preferably 0.05 to 0.8 mg / cm 2 , and even more preferably 0.07 to 0.7 mg / cm 2 , and even more preferably 0.10 to 0.5 mg / cm 2 , and even more preferably 0.10 to 0.3 mg / cm 2 , and even more preferably 0.15 to 0.3 mg / cm 2 It is.

[0033] When the topical agent is a water-in-oil (W / O) type, the amount of metal oxide (A) applied to the skin surface is 0.03 mg / cm from the viewpoint of improving the adhesion suppression effect. 2 or more, preferably 0.04 mg / cm 2 More preferably, 0.05 mg / cm 2 More preferably, 0.07 mg / cm 2 More preferably, 0.10 mg / cm 2 More preferably, 0.15 mg / cm 2 From the viewpoints of economy and usability when used as an external preparation, the concentration is preferably 0.8 mg / cm 2 Less than 0.7 mg / cm, more preferably 0.7 mg / cm 2More specifically, the amount of the metal oxide (A) applied to the skin surface is preferably 0.03 to 0.8 mg / cm from the viewpoint of improving the adhesion suppression effect, as well as from the viewpoints of economy and usability when used as an external preparation. 2 , more preferably 0.04 to 0.8 mg / cm 2 , and more preferably 0.05 to 0.8 mg / cm 2 , and even more preferably 0.07 to 0.8 mg / cm 2 , and even more preferably 0.10 to 0.8 mg / cm 2 , and even more preferably 0.15 to 0.8 mg / cm 2 , and even more preferably 0.15 to 0.7 mg / cm 2 It is.

[0034] In addition to the above-mentioned embodiment, the present invention further discloses the following embodiments. <1> Average primary particle diameter d A A metal oxide (A) having a particle size of 300 nm or less is added at 0.07 mg / cm 2 The above is a method for inhibiting adhesion of atmospheric hazardous substances to the skin by applying the composition to the skin to inhibit adhesion of the atmospheric hazardous substances to the skin. <2> The metal oxide (A) is at least one selected from the group consisting of titanium oxide and zinc oxide. <1> 2. A method for suppressing adhesion of harmful air substances according to claim 1. <3> The metal oxide (A) has a surface that has been subjected to a hydrophobic or hydrophilic treatment. <1> or <2> 2. A method for suppressing adhesion of harmful air substances according to claim 1. <4> The metal oxide (A) has a surface that has been subjected to a hydrophobic treatment. <1> ~ <3> 2. A method for suppressing adhesion of atmospheric hazardous substances according to any one of claims 1 to 11. <5> The hydrophobic treatment is one or more selected from the group consisting of a silicone treatment, an alkylalkoxysilane treatment, and a fatty acid treatment. <4> 2. A method for suppressing adhesion of harmful air substances according to claim 1.

[0035] <6> Average primary particle diameter d of metal oxide (A) A is 80 nm or less. <1> ~ <5> 2. A method for inhibiting adhesion of atmospheric hazardous substances according to any one of claims 1 to 11. <7> Average primary particle diameter d of metal oxide (A)A is 50 nm or less. <1> ~ <6> 2. A method for inhibiting adhesion of atmospheric hazardous substances according to any one of claims 1 to 11. <8> Average primary particle diameter d of metal oxide (A) A is 5 nm or more, <1> ~ <7> 2. A method for suppressing adhesion of atmospheric hazardous substances according to any one of claims 1 to 11. <9> Metal oxide (A) at 0.15 mg / cm 2 The above is applied to the skin. <1> ~ <8> 2. A method for suppressing adhesion of atmospheric hazardous substances according to any one of claims 1 to 11. <10> Metal oxide (A) at 0.8 mg / cm 2 Hereinafter, the above-mentioned <1> ~ <9> 2. A method for inhibiting adhesion of atmospheric hazardous substances according to any one of claims 1 to 11.

[0036] <11> As metal oxide (A), the average primary particle diameter d A 0.07 mg / cm2 of at least one selected from the group consisting of hydrophobically treated titanium oxide and zinc oxide, the particle size of which is 5 nm or more and 300 nm or less. 2 More than 0.8mg / cm 2 The following is a method for inhibiting adhesion of atmospheric hazardous substances to the skin by applying the composition to the skin to inhibit adhesion of the atmospheric hazardous substances to the skin. <12> As metal oxide (A), the average primary particle diameter d A 0.07 mg / cm2 of at least one selected from the group consisting of hydrophobically treated titanium oxide and zinc oxide, 2 More than 0.8mg / cm 2 The following is a method for inhibiting adhesion of atmospheric hazardous substances to the skin by applying the composition to the skin to inhibit adhesion of the atmospheric hazardous substances to the skin. <13> As metal oxide (A), the average primary particle diameter d A 0.15 mg / cm2 of at least one selected from the group consisting of hydrophobically treated titanium oxide and zinc oxide, the particle size of which is 5 nm or more and 50 nm or less. 2 More than 0.8mg / cm 2 The following is a method for inhibiting adhesion of atmospheric hazardous substances to the skin by applying the composition to the skin to inhibit adhesion of the atmospheric hazardous substances to the skin. <14> The hydrophobic treatment is at least one selected from the group consisting of a silicone treatment, an alkylalkoxysilane treatment, and a fatty acid treatment. <11> ~ <13> 2. A method for inhibiting adhesion of atmospheric hazardous substances according to any one of claims 1 to 11. EXAMPLES

[0037] In the following examples and comparative examples, "parts" means "parts by mass" unless otherwise specified.

[0038] (Metal oxide (A) average primary particle diameter d A ) When the metal oxide (A) has a shape other than a plate shape, a dispersion of the metal oxide (A) prepared in advance is placed on the sample stage of a transmission electron microscope (TEM) (trade name "JEM1400Plus", manufactured by JEOL Ltd.), air-dried, and the maximum short diameter of 300 primary particles in an image observed by the TEM at a magnification of 50,000 times is measured, and the number average value is taken as the average primary particle diameter d A Here, the maximum minor axis refers to the minor axis that has the greatest length among the minor axes perpendicular to the major axis. When the metal oxide (A) is plate-like, the thicknesses of 300 primary particles in the image observed under the same method and magnification conditions as above are measured, and the number average value is taken as the average primary particle diameter d A It was decided. The dispersion of metal oxide (A) was prepared by adding 95 g of ethanol as a solvent to 5 g of metal oxide (A) and subjecting the mixture to ultrasonic dispersion.

[0039] (Kinematic viscosity at 25°C) The kinematic viscosity at 25° C. was measured using an Ubbelohde viscometer in accordance with ASTM D 445-46T or JIS Z 8803.

[0040] In the examples and comparative examples, commercially available products of the metal oxide (A) shown in Table 1 below were used.

[0041] [Table 1]

[0042] Examples 1 to 9, Comparative Example 1 The metal oxide (A) and the volatile oil were stirred and mixed at room temperature according to the composition shown in Table 2 to obtain the samples used in Examples 1 to 9 and Comparative Example 1. The volatile oil was dodecamethylpentasiloxane ("KF-96L-2cs" manufactured by Shin-Etsu Chemical Co., Ltd., kinematic viscosity at 25°C: 2 mm 2 / s) was used. The effect of the obtained samples in inhibiting adhesion of harmful air substances was evaluated by the following method, and the results are shown in Table 2.

[0043] Examples 10 to 13, Example 15, Comparative Example 2 3.5 parts of the metal oxide (A) shown in Table 3 and 96.5 parts of ethanol were stirred and mixed to obtain the samples used in Examples 10 to 13, Example 15, and Comparative Example 2, respectively. The effect of inhibiting adhesion of harmful air substances to the obtained samples was evaluated by the following method, and the results are shown in Table 3.

[0044] Example 14 A sample used in Example 14 was obtained by mixing 5 parts of the metal oxide (A) shown in Table 3 and 95 parts of ethanol with stirring. The effect of inhibiting adhesion of harmful air substances to the obtained samples was evaluated by the following method, and the results are shown in Table 3.

[0045] <Method for evaluating the effect of suppressing adhesion of harmful air substances> The samples obtained in the examples and comparative examples were applied to white artificial leather (product name "Laforet S2923", manufactured by Okamoto Shinwa Co., Ltd.) as a skin substitute so as to obtain the application amount of metal oxide (A) shown in Tables 2 and 3, and then left to dry overnight at room temperature. The artificial leather surface coated with the metal compound (A) was exposed to an airflow environment containing the harmful air substances to be evaluated, and the L * a * b * The value was measured, and the color difference ΔE before and after exposure was measured by the following method. [Measurement of color difference ΔE] Using a colorimeter (product name "CM-2002", manufactured by Konica Minolta, Inc.), the L1 * , a1 * , b1 * The values ​​were measured. Separately, a blower (product name "Silky Wind 9ZF002RH02", size: 129 × 106 × 83 mm, manufactured by Rhythm Watch Co., Ltd.) and a mesh sieve (Test sieves JIS Z 8801, frame dimensions: φ100 × 45H, mesh size: 106 μm, manufactured by Tokyo Screen Co., Ltd.) were fixed in a glove bag (product number "3-118-01", manufactured by AS ONE Co., Ltd.). The installation height of the mesh sieve was 17 cm. The artificial leather (5 cm x 4 cm) coated with the metal oxide (A) as a test sample was attached to a support so that the height of the bottom end of the artificial leather was 11 cm. The distance between the coated surface of the artificial leather of the support and the blower was 15 cm, and the blower was installed so that the coated surface of the artificial leather was perpendicular to the direction of airflow from the blower and the center height of the blower blades was the same as the center height of the artificial leather, as shown in Figure 1. The temperature inside the glove bag was set to 25°C and the relative humidity to 57%RH, and 50 mg of graphite powder (product name "J-CPB", average particle size: 5.5 μm, manufactured by Nippon Graphite Industries Co., Ltd.) as the air hazardous substance to be evaluated was classified using a mesh sieve removal brush (product name "JNB-5", brush diameter 53 μm, manufactured by Tokyo Screen Co., Ltd.) and dropped in front of the outlet of a blower with the air blowing scale set to 1 for 1 minute, exposing the surface of the artificial leather coated with metal oxide (A) to the air blowing environment of the air hazardous substance to be evaluated. Next, the L2 of the exposed artificial leather surface was measured using the above colorimeter. * , a2 * , b2 * The value was measured, and the color difference ΔE value was calculated according to the following formula (I). ΔE = [(L1 * -L2 * ) 2 +(a1 * -a2 * ) 2 +(b1 * -b2 * )2 ] 0.5 (I) The above operation was carried out three times for each sample, and the average value of the color difference ΔE of the artificial leather coated with the metal oxide (A) of the test sample was taken as ΔEt. Furthermore, the same operation as above was carried out three times for the artificial leather not coated with the metal oxide (A) as a standard sample, and the average value of the color difference ΔE was taken as ΔEs, and the adhesion inhibition rate was calculated from the following formula (II). The higher the adhesion inhibition rate, the better the effect of inhibiting the adhesion of atmospheric harmful substances. Suppression rate of harmful air substances (%) = 100 × (ΔEs-ΔEt) / ΔEs (II)

[0046] [Table 2]

[0047] [Table 3]

[0048] From Table 2, in Examples 1 to 9, the average primary particle diameter d A The metal oxide (A) having a specific concentration of 0.03 mg / cm 2 It can be seen that the coating amount was so large that it had a higher adhesion suppression effect than Comparative Example 1. From Table 3, in Examples 10 to 15, the average primary particle diameter d A It can be seen that a high adhesion suppression effect is achieved compared to Comparative Example 2 because a metal oxide (A) having a diameter of 800 nm or less was applied in a predetermined amount. [Industrial Applicability]

[0049] The adhesion inhibiting method of the present invention is highly effective in inhibiting the adhesion of atmospheric hazardous substances and is therefore particularly useful as a method for inhibiting the adhesion of atmospheric hazardous substances to the skin. [Explanation of symbols]

[0050] 1: Sample to be evaluated 2:Support 3: Mesh sieve 4: Air hazardous substances for evaluation 5: Blower

Claims

1. Average primary particle diameter d A 0.03 mg / cm of a metal oxide (A) having a particle size of 800 nm or less 2 The above is a method for inhibiting adhesion of atmospheric hazardous substances to the skin by applying the composition to the skin to inhibit adhesion of the atmospheric hazardous substances to the skin.

2. 2. The method for suppressing adhesion of atmospheric hazardous substances according to claim 1, wherein the metal oxide (A) is at least one selected from the group consisting of titanium oxide and zinc oxide.

3. 3. The method for inhibiting adhesion of atmospheric hazardous substances according to claim 1 or 2, wherein the surface of the metal oxide (A) has been subjected to a hydrophobic or hydrophilic treatment.

4. 4. The method for inhibiting adhesion of atmospheric hazardous substances according to claim 1, wherein the metal oxide (A) has a surface that has been subjected to a hydrophobic treatment.

5. Average primary particle diameter d of metal oxide (A) A The method for suppressing adhesion of atmospheric hazardous substances according to any one of claims 1 to 4, wherein the particle size is 5 nm or more.

6. Metal oxide (A) at 0.8 mg / cm 2 The method for inhibiting adhesion of atmospheric hazardous substances according to any one of claims 1 to 5, which comprises applying the composition to the skin.

Citation Information

Patent Citations

  • Skin care cosmetic

    WO2014136993A2